Minimally invasive management of pilonidal sinus disease by phenol intra-cavitary application: A single surgeon experience - Barut, Bora (Annals of Medical Research, 2021)
Aim: The objective of the present study is to share single surgeon’s experience in management of pilonidal sinus disease by phenol application.Material and Methods: Fifty-two patients, who were treated by phenol application for pilonidal sinus disease between September 2010 and August 2013, were analyzed retrospectively.Results: During this period phenol application was performed in 52 patients due to pilonidal sinus disease. Phenol application was performed three times for each patient (1st, 2nd and 7th days). Forty-eight (92%) patients were male and 4 (8%) female with a mean age of 22 years (range: 16-38 y). The mean follow-up period of the patients was 11 months (range: 4-18 m). Three (5.7%) patients had a recurrence and the mean follow up period was 11 months.Conclusion: Many surgical techniques are available in the treatment of pilonidal sinus disease. But all of them remain controversial due to recurrence and complication rates. Phenol treatment is easily applicable and has low costs with acceptable recurrence rates and provides rapid healing. For this reason, we suggest this non-invasive treatment in pilonidal sinus disease.Keywords: Pilonidal sinus disease; phenol; minimally invasive; treatment experience.
Keywords: Pilonidal sinus disease; phenol; minimally invasive; treatment experience.